Cultural orientation and safety app for new and short-term health care providers in Nunavut - Healey Akearok, Gwen; Tabish, Taha; Cherba, Maria (Canadian journal of public health, 2020)
Setting One of the greatest challenges of Nunavut’s health care system is its reliance on short-term professionals, many of whom are not oriented to the Inuit historical/cultural context and the organization of health care in the territory. Our objective was to develop a free iOS/Android app to address this knowledge gap. Intervention We reviewed existing literature and interviewed key stakeholders to develop the content of the app covering the following: Inuit ways of communicating and expectations in the health care setting; Inuit history, settlement, and societal values (including a bibliography and a list of Inuktitut language phrases and resources); health care model (including referral pathways for tertiary care and mental health referrals); maps and community information; and useful information to prepare for your arrival. The app, HealthNU, was launched in September 2017. We targeted new and short-term health care providers in Nunavut, and the app has also been circulated and used by social workers, educators, and health care providers outside of the territory. Outcomes By September 5, 2019, the app had been downloaded more than 700 times. To evaluate the app, we conducted interviews and a brief survey with key stakeholders ( n = 18), who indicated that (1) the app was easy to use; (2) the content was highly relevant and would result in improved cultural competencies; and (3) they would recommend the app to colleagues and were already using it for recruitment/orientation. Challenges and limitations included: ensuring practitioners “completed” all modules while reading/using the app, and low response rate among providers who were solicited for feedback. Implications HealthNU is an example of how technology solutions developed in partnership with community members, health care providers, researchers, and government can improve the quality of care for Nunavummiut. We are currently working with the Nunavut Department of Health to develop similar apps in other contexts.